O agrupamento de escolas como novo escalão da administração desconcentrada - Licínio C. Lima (Universidade do Minho, 2004)
The process of grouping schools stimulated by the XV Constitutional Government resulted in the creation of new "management units", with their own organs within the central school of each group. The development of this policy is the object of analysis in the light of the objectives concerning the recentralization of power, transforming each group of schools, through its central one, into a new rank of administrative deconcentration, i.e., into a new peripheral instance of control over schools.